2012
DOI: 10.1596/1813-9450-5931
|View full text |Cite
|
Sign up to set email alerts
|

Innovative and Absorptive Capacity of International Knowledge: An Empirical Analysis of Productivity Sources in Latin American Countries

Abstract: This paper examines two sources of global knowledge spillovers: foreign direct investments (FDI) and trade. Empirical evidence demonstrates that FDI and trade can contribute to overall domestic productivity growth only when the technology gap between domestic and foreign firms is not too large and when a sufficient absorptive capacity is available in domestic firms. In this paper we propose the terms R&D and Labor quality to capture the innovative and absorptive capacity of the country. The spillovers effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…This finding is in line with the literature since Murovec and Prodan (2009) showed that companies' skills in recognizing and assimilating new knowledge derive, to a large extent, from the individual capabilities of their workers.. Moreover, according to Castillo et al (2011) human capital is important because there is evidence that the positive impacts of the development of FDI flows depend on the high level of human capital. Miguelez and Moreno (2015) comment on the positive role of AC in assimilating knowledge flows from workers' geographical mobility.…”
Section: Randd Activitiessupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is in line with the literature since Murovec and Prodan (2009) showed that companies' skills in recognizing and assimilating new knowledge derive, to a large extent, from the individual capabilities of their workers.. Moreover, according to Castillo et al (2011) human capital is important because there is evidence that the positive impacts of the development of FDI flows depend on the high level of human capital. Miguelez and Moreno (2015) comment on the positive role of AC in assimilating knowledge flows from workers' geographical mobility.…”
Section: Randd Activitiessupporting
confidence: 87%
“…The human capital variable is measured by the average years of schooling for adults over 25 years of age. Castillo et al (2011) Activities in R&D, human capital R&D Activities: The presence of productivity spillovers depends on the investment efforts of local firms in R&D activities. They play an important role in the transfer of knowledge, in addition to its role as a means of innovation.…”
Section: Human Capitalmentioning
confidence: 99%
“…Various studies analyzing regional absorptive capacity that have been conducted are based on quantitative [30,34,37,[48][49][50] rather than qualitative [30,38] research. In this study, were used the explanatory sequential mixed-method approach, where qualitative data collection and analysis follow the quantitative data collection and analysis in the context of a single case study.…”
Section: The Methodological Approach To Assess Absorptive Capacity Ofmentioning
confidence: 99%
“…This in turn hampers a regions’ capability to decode and efficiently exploit new knowledge irrespective of its source. Positive productivity spillovers from FDI and trade only occur when the country has AC in terms of ongoing R&D activity (Castillo et al , 2011). Where trade competition is tough, larger spillovers are in evidence.…”
Section: Proposition Developmentmentioning
confidence: 99%